If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 251 + -17x = -9x + -285 Reorder the terms: 251 + -17x = -285 + -9x Solving 251 + -17x = -285 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 251 + -17x + 9x = -285 + -9x + 9x Combine like terms: -17x + 9x = -8x 251 + -8x = -285 + -9x + 9x Combine like terms: -9x + 9x = 0 251 + -8x = -285 + 0 251 + -8x = -285 Add '-251' to each side of the equation. 251 + -251 + -8x = -285 + -251 Combine like terms: 251 + -251 = 0 0 + -8x = -285 + -251 -8x = -285 + -251 Combine like terms: -285 + -251 = -536 -8x = -536 Divide each side by '-8'. x = 67 Simplifying x = 67
| t=-38-7(52-1) | | -25.5=9(8.5x-6) | | 425=(2h-10)+h | | 4n^2+7n-9=0 | | -18x+50=-22x-126 | | 9y+3x=54 | | -164+2x=363-15x | | 115=x*1.633 | | 115=x*1.63 | | -6x+6(6x-12)=-282 | | 115=x*1.6 | | 115=x*1.6335227 | | 83-24x=-18x-253 | | -24-27x=-26x+23 | | -24-27x=-26+23 | | 26.5=-8.5n-9.5n | | 528=-12(-7x+33) | | 2.3x+4.2y=10.8 | | (x^2+2x*y)dx+x*y*dy=0 | | 660=-10(8x+38) | | sqrt(5x+1)-sqrt(3x-5)=2 | | 3x+4w=13 | | y-x=x-5 | | 6x^2+11x-16=x-8 | | -3x-5(-2x+24)=-64 | | 5x+4=8x+7 | | 24x+81-7x=19 | | -42-18x=98-13x | | t^3-4t^2-5=0 | | W/4=116 | | (4x-1)(2x+3)(x+5)=0 | | 15t=27x^2+12y-23 |